Comunicación oral en inglés en estudiantes de segundo grado de secundaria en dos instituciones educativas de Iquitos 2022 - Pinedo Ramírez, Néstor Moisés (2023)
The main objective of this research was to compare second year students’ oral communication in English achievement at two secondary schools in Iquitos 2022. This study was of a comparative type with field study, contemporary transectional, and univariate designs. The study population was made up by 167 female second-grade students. The data collection tools were a valid and reliable listening test, a speaking test, and rubrics. It was found that the speaking mean score at Sagrado Corazon Public School students is slightly lower than the mean score at Nuestra Señora de Fátima School (8,775 < 9,443), in a 0-20 scale, both being at the beginner level. The study concludes that, according to a parametric t-student test for independent samples, there is statistically significant difference in oral communication in English achievement between both schools, since p-value was 0.002 < α = 0.05.